2006
DOI: 10.1111/j.1525-1314.2006.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐emplacement serpentinization and related hydrothermal metamorphism in a kimberlite from Venetia, South Africa

Abstract: The common serpentine-diopside matrix assemblage in volcaniclastic kimberlite (VK) at the Venetia Mine, South Africa is ascribed to a secondary origin, because of post-emplacement serpentinization and associated hydrothermal metamorphism. Volcaniclastic deposits with 20-30% porosity infill kimberlite pipes in the waning stages of kimberlite eruptions. Olivine macrocrysts are typically rimmed by talc and are pseudomorphed by lizardite, with minor magnetite. The fine matrix consists of mixtures of lizardite, chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 36 publications
4
62
1
Order By: Relevance
“…This restriction also rules out, by definition, the existence of any non-kimberlite diatreme, which we view as a major conceptual problem. And in practice, even for kimberlites, such a restriction is deeply flawed because one of these "defining" characteristics, the microlitic diopside, is proposed by Stripp et al (2006) to be the product of secondary aqueous alteration at temperatures below 370ºC.…”
Section: Kimberlitic Diatremesmentioning
confidence: 99%
See 1 more Smart Citation
“…This restriction also rules out, by definition, the existence of any non-kimberlite diatreme, which we view as a major conceptual problem. And in practice, even for kimberlites, such a restriction is deeply flawed because one of these "defining" characteristics, the microlitic diopside, is proposed by Stripp et al (2006) to be the product of secondary aqueous alteration at temperatures below 370ºC.…”
Section: Kimberlitic Diatremesmentioning
confidence: 99%
“…We are unconvinced by this model for development of tuffisitic kimberlite and tuffisitic kimberlite breccia, and prefer a more conventional fragmentation style. The origin of these textures needs to be interpreted in light of the clear evidence for strong and pervasive alteration (e.g., Stripp et al, 2006;Cas et al, 2008a;Kurszlaukis and Lorenz, 2008).…”
Section: Eruptive Processes Of Maar-diatreme Volcanoesmentioning
confidence: 99%
“…The inter-grain pore-space is filled with isopachous radiating acicular diopside microlites, massive serpentine and clay minerals ( Fig. 10d; e.g., Stripp et al 2006). Country rock xenocrysts include feldspar, amphibole, quartz and biotite.…”
Section: Massive Volcaniclastic Kimberlitementioning
confidence: 99%
“…The diopsideserpentine-calcite assemblages in the pore-spaces of the massive volcaniclastic kimberlite and matrix-supported volcaniclastic kimberlite lithofacies are interpreted as posteruption cements precipitated by hydrothermal fluids that circulated through the hot and porous deposit after the eruption. Recent work by Stripp et al (2006) indicated that the diopside-serpentine assemblage forms at temperatures between ∼250-380°C from meteoric-derived fluids. This assemblage provides a minimum estimate on the emplacement temperature of massive volcaniclastic kimberlite.…”
Section: Partial Excavation Of K2 West and Deposition Of Massive Volcmentioning
confidence: 99%
“…The ratio of the two main volatiles H 2 O and CO 2 and the timing of their exsolution from the magma could vary in different kimberlites affecting their geology (Skinner and Marsh 2004) and diamond population (Fedortchouk et al 2010). Loss of volatiles during kimberlite eruption and development of secondary minerals prior or post-kimberlite emplacement (Mitchell 2013;Stripp et al 2006) hide the primary composition of volatiles. Fluids play the main role in the process of diamond resorption (Fedortchouk et al 2007;Khokhryakov and Pal'yanov 2010), and the morphology of dissolution features on diamond can help to reveal the primary composition of kimberlitic volatiles (Fedortchouk et al 2010).…”
mentioning
confidence: 98%